Evaluating the Effectiveness of the Disaster Preparedness Curriculum on the Intention of Midwifery Alumni to Provide Reproductive Health Services in Crisis Situations: A Planned Behavior Theory Approach - Ayatullah Harun; Ruqaiyah Ruqaiyah; Fatmawati Amir; Rahma Winahyu Jannata; Ikrawanty Ayu Wulandari; Ainun Sri Rahmadhani; Monica Gita Cahyani; Adriyani Adam (Direktorat Politeknik Kesehatan Makassar, 2025)
The background of the problem in 2024 is that disaster victims in South Sulawesi will reach 795,930 people. According to Law Number 24 of 2007 concerning Disaster Management, vulnerable groups in disaster occurrences include infants, toddlers, children, pregnant mothers, lactating mothers, disabilities, and the elderly. These groups often experience greater impacts due to natural disasters The purpose of the study was to evaluate the effectiveness of the disaster preparedness curriculum that has been passed by D3 Midwifery alumni of the Pelamonia Institute of Health Sciences with a planned behavior theory approach by assessing the differences between the two groups of midwifery alumni. The research method uses quantitative methods with observational approaches and comparative design. to compare two groups of midwifery alumni, namely Group A who received a disaster curriculum during college and Group B who did not get a disaster curriculum. Through the theoretical approach of the Theory of Planned Behavior by measuring the differences between the two groups ranging from knowledge, attitudes, perceptions, subjective norms, and intentions of midwifery alumni in providing services in health crisis situations. The results of the study showed significant differences between the two groups for the knowledge variable of the average difference value of 5.44 with a value of p= 0.00 < 0.05. the attitude variable of the average difference value was 6.46 with a value of p= 0.00 < 0.05, the perception variable of the average difference value was 4.58 with a value of p= 0.00 < 0.05. the variable of subjective norms of the average difference value was 5.65 with a value of p= 0.00 < 0.05. the variable of intention of the average difference value of 16.03 with a value of p= 0.00 < 0.05. In conclusion, there are significant differences in the variables of knowledge, attitudes, perceptions, subjective norms and the intention of midwives to provide services in health crisis situations.